Operationalisierung von ,,Beschäftigungsfähigkeit“ – ein methodischer Beitrag zur Entwicklung eines Messkonzepts - Helmut Apel; Michael Fertig (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2009)
– Despite its increasing importance in labour market discourses and programmes an empirical concept for measuring employability is still not available. This paper presents the results of a feasibility study which aims at designing such a concept. It was carried out as a pilot study preparing the methodological approach for measuring individual progress in employability as a potential outcome for the evaluation of the so-called Hartz IV reforms in Germany. Based on an exploratory questionnaire completed by means of a telephone survey of recipients of unemployment benefit (Arbeitslosengeld 1) and individuals in the new benefit system (Arbeitslosengeld 2), six potential dimensions of employability were extracted by principal component analyses (PCA). These dimensions were then used in probit models to test their association with observed employment probabilities. Empirical results suggest a compact set of indicators representing several components of employability which are significantly associated with actual employment. Furthermore, applying these indicators of employability in regression models for employment probabilities, the predictive power of the models increases considerably compared to models with the commonly used socio-demographic characteristics such as age, gender, education or unemployment duration alone.
Keywords: 330; Beschäftigungsfähigkeit - Messung; Indikatorenbildung